Perancangan Sistem Laporan Arus Kas (Cashflow) Pada PT. Tirta Kencana Mulia - Mahsa Savira Berlianti Putri; Yekti Asmoro Kanthi; Adnan Zulkarnain (J-INTECH ( Journal of Information and Technology), 2022)
The cashflow statement provides management information in the form of cash receipts and use within the company, which is stated as one of the main financial statements that must be prepared for economic decision making. The cash flow report presents cash inflows and cash outflows within a company. The cash flow statement consists of three activities, namely operating, investing and financing cash flows. PT. Tirta Kencana Mulia is a company engaged in services and trading. In the service sector, the company is engaged in professional activities as a business consultant, in addition to trading, this company sells on a large scale electronic equipment, security equipment and computer equipment. Problems owned by PT. Tirta Kencana Mulia, which is a discrepancy in the financial statements with the actual conditions that makes the Top Management unable to predict whether the company's finances are doing well or not. This makes the company to plan in the use of information technology in the form of a system, which can accommodate financial management activities according to the formulated SOP. To be able to realize the system, it is necessary to do software engineering with the waterfall method, because the waterfall has advantages when user needs are stable and do not change like the conditions at PT. Tirta Kencana Mulia. In testing the system, the author uses the Blackbox Testing method where this system will be tested functionally whether it is as expected or not. Based on the results of these tests the authors can draw the conclusion that with this system it can facilitate top management in making decisions.